E-Tutor Tandems in a COIL Course – Design, Implementation and Evaluation - Langesee, Lisa-Marie; Ukhova, Nelli (International Journal of Research in E-learning, 2023)
Research on digital collaboration scenarios in Higher Education (HE) is characterized by various approaches that often define the acquisition and development of global skills as learning goals. Virtual Collaborative Learning (VCL) in HE represents one approach to facilitating students’ global skills. Depending on the use case, these learning arrangements can include case study-based group learning under e-tutorial supervision. This paper focuses on the perspective of e-tutors – specially qualified student assistants – and their competence development during the summer semester of 2022. Based on previous research findings, a tandem setting was chosen for their competence development. This paper mainly compares expectations and experiences regarding the competence improvement of e-tutors in a multinational tandem. These expectations and experiences were queried through two quantitative questionnaires utilizing 5-point Likert scales and one short follow-up questionnaire after the finalization of VCL. In general, the positive expectations of the e-tutors were fulfilled, but not to a similar extent for each competence category. Especially the development of social and pedagogical competencies was positive, whereas the development of intercultural competencies was challenging. Several recommendations for action were derived, which impact further e-tutor training.